Analisis Perbandingan Strategi Pembelajaran terhadap Pemikiran Matematika Tingkat Lanjut (Advanced Mathematical Thinking) - Ayu Aristika (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The first problem faced by students is the ability to represent AMT when learning mathematics. In Indonesia, mathematics is a subject that is less popular with most students because it is complicated and difficult to understand. Mathematical material and mathematical thinking skills are two things that continue to develop, namely between mathematical material that is understood and students' mathematical thinking skills that need to be further developed through mathematics learning and mathematical material that continues to be developed more widely. This study aims to compare several AMT learning strategies for students. This study can improve the abilities that students already have to be better. Especially the development of mathematical abilities in students, one of which is AMT ability. Therefore, in learning mathematics, it is necessary to develop students' AMT abilities. The research method used in this study is descriptive analysis. This study also uses a Randomized Pretest Posttest Control Group Design research design. The results of experimental research on the effect of learning strategies on students' AMT abilities. The use of cooperative learning in learning activities in schools has various advantages or benefits. Strength is oriented towards optimal learning activities so that learning objectives can be achieved effectively through the support of lecturers and students in learning. In addition, the selection of learning strategies used by lecturers is greatly influenced by the nature of the subjects to be taught and is also influenced by the level of AMT ability that already exists in students.